High proportion of cactus species threatened with extinction - Abba, Agustín Manuel (2015)
A high proportion of plant species is predicted to be threatened with extinction in the near future. However, the threat status of only a small number has been evaluated compared with key animal groups, rendering the magnitude and nature of the risks plants face unclear. Here we report the results of a global species assessment for the largest plant taxon evaluated to date under the International Union for Conservation of Nature (IUCN) Red List Categories and Criteria, the iconic Cactaceae (cacti). We show that cacti are among the most threatened taxonomic groups assessed to date, with 31% of the 1,478 evaluated species threatened, demonstrating the high anthropogenic pressures on biodiversity in arid lands. The distribution of threatened species and the predominant threatening processes and drivers are different to those described for other taxa. The most significant threat processes comprise land conversion to agriculture and aquaculture, collection as biological resources, and residential and commercial development. The dominant drivers of extinction risk are the unscrupulous collection of live plants and seeds for horticultural trade and private ornamental collections, smallholder livestock ranching and smallholder annual agriculture. Our findings demonstrate that global species assessments are readily achievable for major groups of plants with relatively moderate resources, and highlight different conservation priorities and actions to those derived from species assessments of key animal groups.